Analysis of the Economics of Terrorism in Nigeria: Boko Haram and Movement for Emancipation of the Niger Delta in Perspective - Yahaya, Abubakar (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2015)
Nigeria has been making headlines in the last decade following the activities of Boko Haram and the Nigeria Delta militants due to their terrorist‟s attacks. The economic conditions of Nigeria most especially Poverty, unemployment and literacy level have not reduced commensurate with Nigeria‟s economic development. The rise of terrorist groups such as Boko Haram and Niger Delta militancy has been linked to the poor economic conditions of Nigeria that has persisted over the years. This research aims to find the relationship between poor economic conditions and terrorism in Nigeria. Data on terrorist activities and economic indicators of poverty, unemployment GDP per capita, inflation, and the literacy rate for the period 1970- 2013 will be analysed. A multivariate co-integration analysis will be carried out to determine the relationship between economic conditions and terrorism in Nigeria. The research is structured in five chapters; Chapter one is the introduction and set out the objectives,the research question and hypothesis for research, Chapter two reviews relevant literature in terrorism studies with a focus on the economics of terrorism. Chapter three centres on research design and methodology with particular emphasis on the methodology employed in the conduct of this research. Chapter four covers the data analysis and presentation of the result to test the hypothesis. The final and fifth chapter concludes the research with conclusion and recommendations.Öz:Boko Haram ve Nijerya Deltası militanlarının yaptıkları saldırılarla son on yılda, Nijerya terörist saldırılarını manşetlere taşımaktadır. Fakirlik, işsizlik ve düşük okuryazarlık düzeyi gibi önemli sorunlar Nijerya‟nın ekonomik kalkınmasıyla orantılı olarak değişmemektedir. Boko Haram ve Nijerya Deltası militanları gibi terörist grupların artışı yıllardır devam eden kötü ekonomik koşullarla doğru orantılıdır. Bu tez, Nijerya‟daki kötü ekonomik koşullar ile terörizm arasındaki ilişkiyi bulmayı amaçlamaktadır. Tez için 1970- 2013 yılları arasındaki terörist faaliyetler, ekonomik verilerle fakirlik, işsizlik ve enflasyon oranları ile okuma yazma oranları analiz edildi. Nijerya‟daki ekonomik koşular ile terörizm arasındaki ilişkiyi anlamak için çok değişkenli eş-bütünleşme analizi yapıldı.Tez beş bölümden oluşmaktadır. Birinci bölüm giriş bölümüdür. Tez sorusunu, tezin amaçlarını ve hipotezi içermektedir. İkinci bölüm terör ekonomisi üzerinde durarak terörizmle ilgili literatür çalışmalarından bahsetmektedir. Üçüncü bölüm araştırmanın yürütülmesinde kullanılan araştırma tasarımı ve metodolojik bilgileri içermektedir. Dördüncü bölüm analiz bölümüdür ve hipotezi test etmek için verileri sunmaktadır. Son ve beşinci bölüm ise araştıranın sonucunu ve önerileri içermektedir.
Master of Arts in International Relations. Thesis (M.A.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of International Relations, 2015. Supervisor: Assoc. Prof. Dr. Erol Kaymak.
Keywords: Political Science; International Relations; Economic Conditions and Development - Nigeria; Terrorism; Economic conditions; Nigeria; Co-integration